The Role of BACH2 in T Cells in Experimental Malaria Caused by Plasmodium chabaudi chabaudi AS - Edwards, Chelsea L.; de Oca, Marcela Montes; de Labastida Rivera, Fabian; Kumar, Rajiv; Ng, Susanna S.; Wang, Yulin; Amante, Fiona H.; Kometani, Kohei; Kurosaki, Tomohiro; Sidwell, Tom; Kallies, Axel; Engwerda, Christian R. (Frontiers in Immunology, 2018)
BTB and CNC Homology 1, Basic Leucine Zipper Transcription Factor 2 (BACH2) is a transcription factor best known for its role in B cell development. More recently, it has been associated with T cell functions in inflammatory diseases, and has been proposed as a master transcriptional regulator within the T cell compartment. In this study, we employed T cell-specific Bach2-deficient (B6.Bach2ΔT) mice to examine the role of this transcription factor in CD4+ T cell functions in vitro and in mice infected with Plasmodium chabaudi AS. We found that under CD4+ T cell polarising conditions in vitro, Th2 and Th17 helper cell subsets were more active in the absence of Bach2 expression. In mice infected with P. chabaudi AS, although the absence of Bach2 expression by T cells had no effect on blood parasitemia or disease pathology, we found reduced expansion of CD4+ T cells in B6.Bach2ΔT mice, compared with littermate controls. Despite this reduction we observed increased frequencies of Tbet+ IFNγ+ CD4+ (Th1) cells and IL-10-producing Th1 (Tr1) cells in mice lacking Bach2 expression by T cells. Studies in mixed bone marrow chimeric mice revealed T cell intrinsic effects of BACH2 on hematopoietic cell development, and in particular, the generation of CD4+ and CD8+ T cell subsets. Furthermore, T cell intrinsic BACH2 was needed for efficient expansion of CD4+ T cells during experimental malaria in this immunological setting. We also examined the response of B6.Bach2ΔT mice to a second protozoan parasitic challenge with Leishmania donovani and found similar effects on disease outcome and T cell responses. Together, our findings provide new insights into the role of BACH2 in CD4+ T cell activation during experimental malaria, and highlight an important role for this transcription factor in the development and expansion of T cells under homeostatic conditions, as well as establishing the composition of the effector CD4+ T cell compartment during infection.